Mental Accounting dan Dilematika Culture Shock Transisi Perkuliahan Online Ke Offline: Studi Fenomenologi Mahasiswa Perantauan - Liliana Cindy; Markus Uhun; Petra Ananda Maryono; Rafles Ginting; Khristina Yunita (Jurnal Akuntansi Publik Nusantara, 2024)
Culture Shock is defined as an excessive feeling of fear and anxiety when in a new environment. This dilemma is experienced by overseas students when lectures are conducted offline, namely how students who come from outside pontianak manage their finances and habits during online lectures. The purpose of this study is to determine how mental accounting affects overseas students directly or indirectly in managing their finances while attending offline lectures. Data collection was carried out using the In-Depth Interview method, Observation, Audio-Visual Material. While data analysis uses data reduction, data presentation, and conclusion drawing. The research sample used 10 accounting students in semester 7 who came from outside of pontianak. The results showed findings that mental accounting is indirectly applied by overseas students by recording, and grouping expense items